Cultural Aspects of Waste Management in Poland and China - TACZKOWSKA, Kalina Maria; BORKOWSKI, Maciej (Journal of Environmental Management and Tourism, 2023)
The main aim of this article was to present differences in the social determinants of waste management and environmental protection in Poland and People's Republic of China. A research gap was identified related to the small number of studies comparing China and Poland in the field of waste management. A systematic review of the literature on waste management and society's approach to environmental protection was conducted, with particular emphasis on municipal waste. The article uses data from local databases, i.e. the Central Statistical Office (GUS) in Poland and The Ministry of Ecology and Environment of the People's Republic of China, as well as data from the World Bank and OECD. The method of comparative analysis and Hofstede's tool were used for selected aspects of the social approach to waste management in Poland and the People's Republic of China. Empirical research was conducted in August 2023. Literature review based on key groups of social factors that differ in the analysed countries. These include those related to purity, religious beliefs, respect for nature, responsibility and ecology. Chinese citizens approach the power supply in their environment in a more collective way than in Poland. The European Union's recommendations has positively affected management of municipal waste in Poland, while in People's Republic of China legislation is constantly updated. In the authors' opinion, in subsequent studies it is worth focusing on comparing other countries in terms of their social approach to environmental protection, as well as conducting surveys.